The whole truth writing fearless nonfiction - Higgins, Nadia (North Mankata, Minnesota Capstone Press, an Capstone imprint, 2016)
"Introduces and defines essential elements of writing nonfiction accompanied by compelling writing prompts for practicing new skills. Real-life author bios and excerpts enhance skills and understanding"--
Arts
Includes bibliographical references and index
1 2 13
Keywords: Creative nonfiction -- Authorship -- Juvenile literature